2023
DOI: 10.1021/acs.analchem.3c02707
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Profiling for Determination of the Time since Deposition of Biofluids in a Forensic Context: A Proof-of-Concept for Urine, Saliva, and Semen in Addition to Blood

Tom D. Schneider,
Thomas Kraemer,
Andrea E. Steuer

Abstract: In a criminal trial, the reconstruction of a crime is one of the fundamental steps of the prosecution process. Common questions, such as what happened, where and how it happened, and who made it happen, need to be solved. Biological evidence at crime scenes can be crucial in the determination of these fundamental questions. One of the more challenging riddles to solve is the when? A trace left at a crime scene can prove a person’s presence at the crime scene. Knowledge about when it was deposited there, the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…However, the authors still concluded that using VAMS with capillary blood samples can capture biological differences of interest not found in plasma samples. 12 Conversely, Schneider et al 94 compared the use of DBSs with other body fluids and dried spots usually found in crime scenes aiming to find a universal biomarker and determine time since deposition.…”
Section: Very Long-chain Acylcarnitine Dehydrogenase Deficiency [Vlca...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the authors still concluded that using VAMS with capillary blood samples can capture biological differences of interest not found in plasma samples. 12 Conversely, Schneider et al 94 compared the use of DBSs with other body fluids and dried spots usually found in crime scenes aiming to find a universal biomarker and determine time since deposition.…”
Section: Very Long-chain Acylcarnitine Dehydrogenase Deficiency [Vlca...mentioning
confidence: 99%
“…From the blood-specific compounds, they verified that four of them (L-phenylalanyl-L-alanine, 3-indole acrylic acid, spermidine and argininosuccinic acid) could be used to monitor time since deposition dynamics over 4 weeks. 94 Two studies used untargeted metabolomics on DBSs to discover potential biomarkers for metabolic diseases associated with fatty acid β-oxidation: very VLCADD and MCADD. 95,96 The authors compared DBS samples from newborns positively diagnosed with the specific disorder against healthy controls.…”
Section: Very Long-chain Acylcarnitine Dehydrogenase Deficiency [Vlca...mentioning
confidence: 99%
See 2 more Smart Citations